Correlation Between Stress Levels and Eating Behavior in College Students: A study at The Faculty of Health Sciences - Ilma Fauzia Muhaimin; Dyah Intan Puspitasari; Endang Nur Widiyaningsih; Listyani Hidayati (Jurnal Gizi Prima (Prime Nutrition Journal), 2023)
Background: The demanding schedules of students within the Faculty of Health Sciences and their substantial course loads frequently lead to elevated stress levels among students. Stress can manifest positive and negative impacts on an individual's eating behavior. This study aimed to establish a correlation between stress levels and eating behavior in students enrolled at the Faculty of Health Sciences, Universitas Muhammadiyah Surakarta.Research Methods: A cross-sectional research design was employed, involving 88 students from the 2019 Faculty of Health Sciences, Universitas Muhammadiyah Surakarta class as the respondents. Stress levels were assessed using the Perceived Stress Scale (PSS-10) questionnaire while eating behavior data were gathered through the Adult Eating Behavior Questionnaire (AEBQ). The Pearson product-moment correlation test examined the relationship between stress levels and eating behavior. Research Result: Among students of the Faculty of Health Sciences, Universitas Muhammadiyah Surakarta, in the 2019 class, 79.5% exhibited moderate stress levels. Regarding eating behavior, 54.5% of these students approached food, while 45.5% tended to avoid food. Notably, 54.5% of students from the Faculty of Health Sciences displayed mild levels of stress alongside an inclination toward approaching food in their behavior. The Pearson product-moment correlation test revealed a statistically significant relationship between stress levels and eating behavior, with a significance value of <0.05. Conclusion: This study establishes a significant correlation between stress levels and eating behavior among students at the Faculty of Health Sciences, Universitas Muhammadiyah Surakarta. Students must develop effective stress management strategies that are closely linked to regulating their eating behavior.